Awareness of effectiveness of shari'ah scholars role in corporate governance of Islamic financial institutions in Malaysia - Adoum, Ali (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2014)
The role of Shari' ah committee and Shari' ah review towards effective governance of Islamic Financial Institutions is that the Shari' ah committee executes fiduciary duties to all the stakeholders of the Islamic Financial Institutions. Similarly, Shari'ah review board of Islamic Financial Institutions is to assist Muslims in abiding to their religious values by ensuring that the Islamic Financial Institution's products are ultimately Shari' ah compliant. The purpose of this wholly qualitative research study was to explore the role and importance of Shari' ah committee and Shari' ah review in Corporate Governance of Islamic Financial Institutions in Malaysia excluding Islamic Insurance companies or Takaful companies. Data for the study was elicited through interviewing and document analysis and purposive sampling technique was utilized to select the respondents. The interview data analysis was performed by using a qualitative method which involved identifying interview themes, comparing the participant's views and determining the commonality among their views. Emergent themes included: Corporate and Shari'ah Governance, Role of Sharl'ah Committee, Product Compliance and Innovation, Shari'ah Compliant Review and Shari'ah Report Adequacy. The findings amongst other things indicated that Shari'ah review and Shari' ah committee of Islamic financial institutions play a role of overseeing that all operational process of the bank are Shari'ah Shari'ah compliant and that the Board of Director members need to be conversant with Islamic finance which is the critical indicator of corporate Governance. In conclusion, Shari'ah Governance has yet to be recognized by the Shari' ah scholars.